The Feasibility of Using Agarophyte Processing Waste - Ignatova, Tatiana A.; Strokova, Nataliya G.; Roshchina, Anna N. (KnE Life Sciences, 2022)
When agarophytes are processed, 16-89% algal waste (AW) is formed. Due to the high content of minerals in this waste and the presence of proteins that are resistant to the action of proteolytic enzymes, such AW is mainly used in the production of feed for farm animals. The significant content of polysaccharides in dry AW indicates that it could be used as a raw material for the production of dietary fiber (DF). Due to the difference in the chemical composition of AW depending on the type of red algae, different approaches for its deproteinization have been used. Thus, a 3% alkali solution should be used for the deproteinization of algal waste from the red algae Gracilaria, a 0.5% alkali solution for GelidiumAW, and a 1% sodium carbonate solution for A. plicataAW.The duration of the deproteinization process is 30 min at a temperature of 97±2 ∘C for all types of AW. In this study, functional and technological solutions of DF from AW were developed. The results showed that their water binding capacity was 6-22 g of water per 1 g of the preparation, the fat binding capacity was 1.6-3.3 g of fat per 1 g of the preparation, and the swelling capacity was 46-312% depending on the type of red algae.The obtained DF was used in the production of minced fish food products of the ‘fish sticks’ type, based on minced fish and consisting of cod and pink salmon. The study of the chemical composition and calorie content of the developed food product showed the possibility of its use in dietary nutrition. Keywords: red algae, algal waste, deproteinization, dietary fiber